Frontispiece: Alloying Behavior of Self‐Assembled Noble Metal Nanoparticles. Issue 38 (6th September 2016) - Kühn, Laura; Herrmann, Anne‐Kristin; Rutkowski, Bogdan; Oezaslan, Mehtap; Nachtegaal, Maarten; Klose, Markus; Giebeler, Lars; Gaponik, Nikolai; Eckert, Jürgen; Schmidt, Thomas J.; Czyrska‐Filemonowicz, Aleksandra; Eychmüller, Alexander
Abstract : Noble Metal Alloys The combination of STEM EDX, XRD, and EXAFS data analysis drew a coherent picture of the characteristic alloying behavior of various bimetallic nanostructured aerogels with an atomic ratio of 1 : 1, which were synthesized by a two‐step gelation process at low temperature. Elemental mapping revealed that only the Au–Ag system exhibits a complete alloy formation in the as‐synthesized state. Unlike Au–Ag, Pt–Pd aerogels formed an unexpected Pd‐based network with embedded Pt particles. The assembly of Au and Pd nanoparticles even resulted in an unforeseen Pd‐shell formation around the Au particles. For more information see the Communication by A. Eychmüller et al. onpage 13446 ff.